PERMITTING POLICY FOR THE REGULATION OF COMMUNITY ACTIVITIES: A STUDY AT POLRESTA BANDAR LAMPUNG - Putri, Arum Monica; Duadji, Noverman; Faedlulloh, Dodi (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
This study aims to analyze the implementation of the permitting policy for regulating community activities within the jurisdiction of Polresta Bandar Lampung and to examine the factors hindering the implementation of the permitting policy using a qualitative approach. Based on Edward III's (1980) policy implementation theory, the research findings indicate that the implementation of the permitting policy for community activity regulation at Polresta Bandar Lampung is not yet optimal. Only the aspects of disposition and resources show positive results, while the communication aspect, particularly in information transmission, has not been optimal, and fragmentation within the bureaucratic structure has not been addressed. Several hindering factors identified include applicants arriving unexpectedly with incomplete requirements, which prolongs the time needed to complete the necessary documents, as well as unclear or unofficial task assignments. Improvement efforts are needed to enhance the effectiveness of the licensing policy implementation.